Psychological benefits of water exercise for low back pain patients - Sugano, A.; Nomura, T.; Kerr, J. H. (Biomechanics and Medicine in Swimming VIII, 1999)
The purpose of the present study was to assess the psychological benefits of water exercise for low back patients. Twenty nine subjects (mean age= 61.4yrs, duration of pain= 12.3yrs) who suffered from low back pain participated in water exercise for 8 weeks. The Tension and Effort Stress Inventory (TESI) was used to measure possiple changes in mood pre- to post-water exercise. In addition, the Oswestry Low Back Disability Questionnaire (ODQ) and the visual analogue scale 01 AS) were used to measure symptoms of back pain. The results showed significant increases in the TESI individual moods relaxation and gratitude after 4 (p<.05) and 8 weeks (p<.Ol) and anxiety showed a significant decrease after 8 weeks of water exercise (p<.05). Significant improvements were also found with ODQ scores (p<.Ol) and VAS scores (p<.OOOl) pre- to post-water exercise. It was suggested that water exercise has psychological benefits such as decreasing anxiety and increasing relaxation for low back pain patients.